MODEL RANCANG BANGUN VIRTUAL TOURISM DI OBJEK WISATA AIR TERJUN GOA GONG, DESA SULANGAI, BANJAR BATULANTANG, KECAMATAN PETANG, KABUPATEN BADUNG - Ida Bagus Nyoman Krisna Prawira Yuda; I Wayan Kiki Sanjaya; Francisca Titing Koerniawaty; I Nengah Subadra (Journal of Tourism and Interdiciplinary Studies, 2023)
This research discusses enjoying tourist attractions with virtual tourism in Sulangai Village, Bali, especially at Goa Gong waterfall tourist attraction. In the situation of a tourist attraction that is classified as a new category, the Sulangai Village Government chooses virtual tourism as a 4.0 promotional media to increase the number of domestic and foreign tourist arrivals. Tourist visit data from January to July 2022 was used to see changes in the number of tourist arrivals during that period. The research method used in this study is a qualitative method. Data collection was carried out by interview, observation and documentation. The study found out conclusions such as (a). There are tourist attractions, tourist facilities, accessibility, and additional tourist services that are quite adequate, (b). Processing of 360o virtual tour website applications uploaded to a free domain website called wix.com. However, the limitations in this study are (a). There is lack budget for making a 360o virtual tour, (b). Human resources in the IT department of the Sulangai Village Government have not fully mastered the making of 360o virtual tours, and (c). The attractions provided by this object are not enough for 360o video shooting. With this research, it is hoped that virtual tourism can provide a more pleasant and attractive appearance for potential tourists so that it can promote this tourist attraction even further